Genomic analysis and antimicrobial resistance in human- and poultry-derived Campylobacter jejuni isolates from Hangzhou, China - Yang, Mingfang; Wang, Xin; Zheng, Luping; Zhu, Yongli (Frontiers in Microbiology, 2025)
Campylobacter jejuni (C. jejuni) is a zoonotic pathogen and is the most prevalent foodborne pathogen globally. The increasing antimicrobial resistance and gene mutation pose a threat to public health and trigger us to enhance surveillance. This study illustrated the antimicrobial resistance profiles, virulence factors, and multilocus sequence typing (MLST) profiles of 47 C. jejuni isolates collected from human stool and raw poultry meat samples between 2022 and 2023 in Hangzhou, China. Notably, 88.9% (16/18) human-derived and 82.9% (24/29) poultry-derived C. jejuni displayed multidrug resistance (MDR) profiles, nalidixic acid + ciprofloxacin + tetracycline was prevalent among them. Relatively high rates of resistance to florfenicol were observed in C. jejuni, 38.9% (7/18) from human sources and 44.8% (13/29) from poultry sources. Comprehensive Antibiotic Resistance Database (CARD) and ResFinder database showed gyrA (T86I) was the dominant factor in quinolones resistance while a rare gyrA (T86V) was found in one poultry-derived C. jejuni. All 37 tetracycline-resistant C. jejuni strains harbored the tet(O) gene. All 20 florfenicol-resistant C. jejuni did not have any related genes. Several key virulence factor genes associated with adherence (cadF, pebA, jlpA, and porA), invasion (CiaB and CiaC), capsule biosynthesis/transport genes (kpsF, kpsD, kpsE, kpsM, kpsC, and Cj1419c) and lipooligosaccharide (LOS) biosynthesis genes (Cj1135, waaV, waaF, htrB, gmhA, and gmhB) were conserved in C. jejuni. MLST analysis revealed high genetic diversity, identifying 28 sequence types (STs), including 3 novel STs, 20 of which belonged to 10 clonal complexes (CCs), and 8 were unassigned. CC-464 and CC-21 strains carried the most virulence genes, correlating with clinical severity, yet represent a minority in local isolates. The most abundant CCs were CC-443 (21.3%, 10/47) and CC-574 (19.1%, 9/47), mainly isolated from poultry. These findings highlight that C. jejuni isolates in Hangzhou had high genetic diversity and MDR, CC-443 and CC-574 were the predominant strains. It is necessary to monitor human-poultry transmission and emerging resistance phenotypes.